Delay Development Et Causa Premature Baby - Tuty Swarni Sinaga (International Journal of Community Service Implementation, 2024)
Children are the dream of the family besides that every family also expects their children to grow optimally (physically, mentally, cognitively and socially healthy) can be proud of and useful for the nation and the nation.As an asset of the nation, children must receive attention from the womb until they become adults.Growth and development is a continuous process that occurs starting from conception and continues until adulthood.. In this study the authors used a quasi experiment with pre and post test design techniques, involving several children with delayed development as samples and techniques measured through the GMFM (Gross Motor Function Measurrement) , which has 5 stages / levels in ability and impairment limitation.The objectives of this activity are:. The objectives of this activity are: to achieve child growth and development in physical and functional capacity according to age, to improve the health status of children in terms of physical and functional capacity, to prevent more severe physical disability of children, to catch up with child growth and development according to the age of development of physical and functional capacity of children, to study factors related to child growth and development